The Jurisprudence on Regional and International Tribunals Digest - Law Africa (Law Africa, 2007)
Summary:The Jurisprudence on Regional and International Tribunals Digest is borne out of the recent developments in the judicial arena of the East African Community and other inter-state arrangements where matters are increasingly getting litigated and determined at the international fora. With such a development, there is the more current need to document the reasoning, not just of judicial officers from the East African Court of Justice but also from other regional and international tribunals. This will help in consolidating knowledge on diverse aspects of substance and procedure from these tribunals for both academic and practice purposes. This digest no doubt adds value to practitioners in the East African region and beyond who are getting absorbed into legal practice before tribunals of an international law character. It is hoped that the digest will further be of great assistance to the community of the academia that is in need of material for the dispensation of knowledge in the area of international law